2006
DOI: 10.1007/0-387-34224-9_22
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Face Registration Errors on Recognition

Abstract: Abstract. Face recognition systems detect faces in moving or still images and then recognize them. However, face detection is not an error-free process, especially when designed for real-time systems. Thus the face recognition algorithms have to operate on faces that are not ideally framed. In this paper we analyze quantitatively the impact of face detection errors on six different face recognition algorithms. Hence, we propose a matching of face recognition algorithms with face detector performance, which can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 13 publications
0
34
0
Order By: Relevance
“…The second difference is, the manual eye center labels, which have been used for alignment is more precise in the artificially occluded face images, whereas due to sunglasses, manual eye center labels of the face images from the AR face database is not reliable. Recent studies on the impact of registration errors on face recognition performance [16,17] lead us to hypothesize that the second difference has more dominant effect. By utilizing an alignment approach [22], which is insensitive to imprecise facial feature localization, we run the experiments again and obtained very high increase in the performance indicating that the main reason causing the performance drop is not the missing eye region information, but the misalignment due to erroneously localized facial feature points.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The second difference is, the manual eye center labels, which have been used for alignment is more precise in the artificially occluded face images, whereas due to sunglasses, manual eye center labels of the face images from the AR face database is not reliable. Recent studies on the impact of registration errors on face recognition performance [16,17] lead us to hypothesize that the second difference has more dominant effect. By utilizing an alignment approach [22], which is insensitive to imprecise facial feature localization, we run the experiments again and obtained very high increase in the performance indicating that the main reason causing the performance drop is not the missing eye region information, but the misalignment due to erroneously localized facial feature points.…”
Section: Discussionmentioning
confidence: 99%
“…This implies that, there is another underlying problem, in addition to missing eye region information. Recently, some studies have been conducted on the robustness of face recognition algorithms against registration errors [16,17]. These studies have shown that face recognition algorithms' performance rely on face alignment accuracy.…”
Section: Ar1scarfmentioning
confidence: 99%
See 1 more Smart Citation
“…As most generic face recognition approaches do not explicitly model local deformations, face registration errors can have a large impact on the system performance [18]. In contrast to the manually aligned database setup, a second database setup has been generated where the faces have been automatically detected using the OpenCV implementa- Modular PCA [22] 14.14 Adaptively weighted Sub-Pattern PCA [22] 6.43 DCT [4] 4.70 tion of the Viola & Jones [23] face detector.…”
Section: Conditions and Resultsmentioning
confidence: 99%
“…And the man-made variations are mainly due to the imperfections of the capture devices and image processing technologies, e.g. the noises from the cameras and the face registration error resulting from imperfect face detections [1]. The performances of many recognition algorithms degrade significantly in these cases.…”
Section: Introductionmentioning
confidence: 99%